Efficacy of sodium formate as a technological feed additive (hygiene condition enhancer) for all animal species. (15th March 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: In 2015, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) issued an opinion on the safety and efficacy of formic acid, ammonium formate and sodium formate as feed hygiene agents for all animal species. In this opinion, two forms of the additive sodium formate, a solid form (specified to contain ≥ 98% sodium formate (w/w)) and a liquid form (specified to contain a minimum of 15% sodium formate, a maximum of 75% free formic acid and a maximum of 25% water), were assessed. Sodium formate was considered safe for all animal species at a maximum concentration of 10, 000 mg formic acid equivalents/kg complete feed (with the exception of pigs, for which a maximum concentration of 12, 000 mg formic acid equivalents/kg complete feed was considered safe). Sodium formate was also considered safe for the consumer and the environment. The Panel also concluded that sodium formate is corrosive. The Panel also concluded that 'for sodium formate, limited data are available to demonstrate their effects in feed'. In the current opinion, additional data to demonstrate the efficacy of sodium formate liquid as a hygiene condition enhancer in feed for all animal species were assessed. The Panel concluded that sodium formate liquid has the potential to be efficacious as hygiene condition enhancer in feedingstuffs for all animal species at the proposed use level.